28 Automatic aortic annulus sizing by the heart navigator III software in the planning of transcatheter aortic valve implantation (TAVI). (4th June 2021) - Carande, Elliott; Chase, Alexander; Hailan, Ahmed; Khurana, Ayush; Smith, Dave; Obaid, Daniel
Abstract : Background: Transcatheter aortic valve implantation (TAVI) requires assessment of gated CT images for accurate aortic annulus sizing. We investigated the accuracy of The Heart Navigator III software (Philips Healthcare, Netherlands) in performing fully automatic annulus measurements. Methods: One-hundred and sixty patients underwent gated cardiac CT scans as pre-assessment for a TAVI procedure. The Heart Navigator III software (Philips Healthcare, Netherlands) performed automatic segmentation of the aortic root and measurement of the aortic annulus area in systole without operator intervention. These were compared with manual measurements made by an experienced CT operator during pre-procedural planning with commercially available CT software. We then evaluated whether the automated measurements would lead to the same valve size selected as the human-operator utilising commonly used TAVI manufacturers. Results: When Heart Navigator III automatic measurements of the aortic annulus size were compared to CT human-operator images, there was a bias of -1.48mm 2 . 95% limits of agreement were from -96.16 to +93.21 mm 2 (see figure 1 ). Automatic measurements and CT human-operator measurements led to the same size Edwards Sapien valve in 71.3% of patients, Abbott Portico valve in 60.6% of patients, Medtronic Evolut in 71.3% of patients and NVT Allegra in 68.8% of patients. The Heart Navigator III selected valves within 1 size of the human-operator choice in 97.1 – 99.4% of cases ( table 1 ) . Conclusion: The Heart Navigator III software (Philips Healthcare, Netherlands) is a promising technology allowing fully automated aortic annulus segmentation and sizing. However, at present the accuracy is not sufficient for clinical use and human-operator oversight is still required. Conflict of Interest: None